2012
DOI: 10.1109/tla.2012.6142483
|View full text |Cite
|
Sign up to set email alerts
|

GeoHealth: A Georeferenced System for Health Data Analysis in Primary Care

Abstract: Abstract-The Primary Care Information System (SIAB) concentrates basic healthcare information from all different regions of Brazil. The information is collected by primary care teams on a paper-based procedure that degrades the quality of information provided to the healthcare authorities and slows down the process of decision making. To overcome these problems we propose a new data gathering application that uses a mobile device connected to a 3G network and a GPS to be used by the primary care teams for coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The GeoHealth has been the target of many studies over the last years, so that further information can be found in the original material [3,4,8,29], as well as in a comprehensive description in Multimedia Appendix 1 [40,41]. For the readers’ convenience, the data flow diagram presented in Figure 3 shows how personal information is handled by the different subprocesses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GeoHealth has been the target of many studies over the last years, so that further information can be found in the original material [3,4,8,29], as well as in a comprehensive description in Multimedia Appendix 1 [40,41]. For the readers’ convenience, the data flow diagram presented in Figure 3 shows how personal information is handled by the different subprocesses.…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, the privacy analysis is particularly grounded on the GeoHealth system. GeoHealth has been targeted in various scientific publications over the years, including work about the design process [8,29], large-scale deployment [3], and CHWs’ experience with the technology [4], which enables us to perform the PIA on the basis of published material, as well as previous first-hand experience with the system.…”
Section: Introductionmentioning
confidence: 99%